Pengaruh Zakat Produktif Terhadap Tingkat Pendapatan Mustahik Kabupaten Banyuwangi: (The Effect of Productive Zakat on Mustahik Income Level in Banyuwangi District) - Sebastiana Viphindrartin; Fiqi Hidayatu Ulfa Haris; Akhmad Munir (UPT Penerbitan Universitas Jember, 2021)
The purpose of this study was to determine the effect of productive zakat mustahik on increasing mustahik's income in BAZNAZ Banyuwangi Regency. This research is a research that uses a quantitative approach that was carried out at BAZNAS Banyuwangi Regency in 2021 using multiple linear regression analysis method with a sample of 50 respondents. Sources of data was obtained through primary and secondary data. Primary data was obtained from the results of the distribution of questionnaires distributed to mustahik. The questionnaire given relates to the target variable for zakat distribution and the guidance given to mustahik. While secondary data is obtained from reading sources and various sources of reports, notes, documents and literature studies obtained from the results of previous research. As for the results of the t-test that has been carried out, the researchers found that the utilization of productive zakat funds had a positive and significant effect on the income level of mustahik.